SACRALITY AND SYMBOLISM OF THE BARIS KLEMAT DANCE AT PURA MENEGA, SESEH CEMAGI TRADITIONAL VILLAGE, BALI: AN ETHNOAESTHETIC STUDY - Ni Putu Putri Laksmi Dewi; Ni Made Ruastiti; Ni Made Arshiniwati (RADJA PUBLIKA, 2025)
Baris Klemat Dance is an aesthetic expression imbued with sacred and symbolic values within the religious rituals of the customary community in Seseh Cemagi Village, Bali. This study aims to examine the presentation structure, symbolic meanings, and sacred dimensions of Baris Klemat Dance, as well as how the local community internalizes these meanings in ritual practice. A qualitative method with an ethnoaesthetic approach was employed, using participatory observation, in-depth interviews, and literature review. The analysis was guided by the theories of Dance Structure (Kaeppler, 2007), Ethnoaesthetics (Merriam, 1964), and Symbolic Meaning (Turner, 1967). The findings reveal that Baris Klemat Dance is presented in a non-narrative form (without storyline), using